Monitoring environmental effects of marine fish aquaculture - Telfer T.C.; Beveridge M.C.M. (Environmental impact assessment of Mediterranean aquaculture farms, 2001)
As mariculture production increases in both northern and southern Europe its conflict with other users of the marine environment, for space and other environmental services, becomes ever greater. Implications of these increases and conflicts require that careful environmental management of aquaculture practices be considered, which rely heavily on the process of monitoring. Monitoring studies for estimation environmental effects follow directly on, and may be considered a progression of, the process of Environmental Impact Assessment. In this paper the reasons for monitoring environmental impacts of aquaculture will be addressed, particularly assessing its use in different physical environments where management practices may vary, and its use in implementing environmental regulation and Environmental Quality Standards. Presently used methods of monitoring impacts of marine cage aquaculture will be described and discussed, the usefulness of the results, and the future of monitoring employing new developments in survey techniques.
TECAM Seminar on Environmental Impact Assessment of Mediterranean Aquaculture Farms, 2000/01/17-21, Zaragoza (Spain)